Relationship of Cow Size to Nutrient Requirements and Production Management Issues: AN226/AN226, 8/2009 - Hersom, Matt (EDIS, 2009)
Proper nutritional status is critical for optimal production efficiency in the beef cow herd. Meeting the nutrient requirements of the productive cow is a prime factor in reproductive success and overall herd profitability. However, beef producers often take a "one size fits all" approach when feeding the cow herd. This singular approach to nutrient supply can have nutritional and economic ramifications. Nutritional requirements vary with age, breed, sex, body condition, environment, physiologic status, and weight. By acknowledging these differences in nutrient requirements, management strategies can be implemented to optimize pasture forages, feed resources, and overall production. While there are many factors that affect nutrient requirements, body size (weight) and milk production are the two primary factors impacting on nutritional requirements. Therefore, this report focuses on cow weight, acknowledging that milk production is an additional driving factor for nutritional requirements of beef cows.